An Integrated Academic Administrative Model for Schools in the Children and Youth Strengthen Projects for the Quality Life in Bangkok Area under the Initiative of Her Royal Highness Princess Maha Chakri Sirindthorn - Chatapun, Pornnicha; Sikkhabandit, Sowwanee; Sriprasertpap, Khwanying (Rajapark Journal, 2022)
The objectives of this research were to develop an integrated academic administration model for schools in the capacity building program of children and youth for a good quality of life in the Bangkok area. The quantitative and qualitative research study was conducted in 3 steps: 1. Study the current condition. Requirements and operational guidelines for integrated academic administration for schools in the project; 2. Create an integrated academic management model for schools in the project; and 3. Evaluate the efficiency of the academic management model for schools in the project. The research instrument was a semi-structured interview form. The group conversation record form and the questionnaire were analyzed by the percentage, mean and standard deviation, and content analysis. The results of the research revealed that the integrated academic administration model for schools in the capacity-building program of children and youth for a good quality of life looks like a mix of children’s and youth empowerment projects. for a good quality of life According to the Child and Youth Development Plan in the Wilderness No. 5, 2017 – 2026, with activities in academic administration in 5 areas, consisting of 1) educational institution curriculum management, 2) learning management, 3) supervision academic work within the school, 4) academic evaluation and assessment, and 5) Development of media, innovation, technology and learning resources. The results of the evaluation of the model's efficiency revealed that the usefulness and feasibility of applying the model were at a high level.